INFERTILITY SCREENING - Rizani Amran; Kms Yusuf Effendi; Iskandar Zulqarnain; Heriyadi Manan; Fatimah Usman; M Komarul Hakim; Vicela Patricia; Selly Rizany; Anton Rama; Achmad Fachroni (Conferences of Medical Sciences Dies Natalis, 2021)
Infertility is a common condition caused by the female factor, male factor, or both. Infertility problems can have a significant impact on married couples who experience them. In addition to causing medical problems, infertility can also cause economic and psychological problems. Couples who experience infertility will undergo a long process of evaluation and treatment, where this process can be both physical and psychological for the infertile couple. The aim of this article is presenting a literature study on infertility screening. Infertility affects millions of people of reproductive age worldwide and impacts family and community life. Estimates suggest that between 48 million couples and 186 million people are living with infertility. Infertility occurs in 15% of couples. Female factors cause infertility in 50-70%, and malefactors are the cause of infertility in 40-50% of couples. Given the high prevalence of malefactors in infertility heterosexual couples, medical history and early evaluation of male partners are needed. Ovulation dysfunction was defined as a history of oligomenorrhea or amenorrhea, recurrent luteal progesterone levels of less than 3 ng/mL, or both. For many women, a menstrual history is sufficient to assess ovulatory function. The clinical history can be used to assess the ovulatory cycle as most women will have regular menstrual cycles every 25–35 days. Anovulation may be associated with obesity, hypothalamic and pituitary dysfunction, PCOS, and other etiologies. Polycystic ovary syndrome is the most common cause of ovulatory infertility. Women with PCOS who have been diagnosed are at increased risk of the metabolic syndrome associated with cardiovascular events and negatively impacting pregnancy. Infertility is the failure of a couple to get pregnant for at least 12 months having regular sex without contraception, or also known as primary infertility. Secondary infertility is the inability of a person to have children or maintain a pregnancy. Idiopathic infertility refers to infertile couples who have undergone standard examinations, including ovulation tests, tubal patency, and semen analysis with normal results.